Characteristics of simplicia ginger (Zingiber officinale) and lemongrass (Cymbopogon citratus) powder by different drying method. Issue 2 (July 2021) - Khaerunnisa; Mahendradatta, M; Asfar, M
Abstract: This study aimed to produce qualified simplicia of ginger and lemongrass powder by determining water content, antioxidant activity, and the characteristic of color and aroma. Two stages of drying were conducted, namely, the conventional method using open-air sun drying and the oven method with a temperature of 50°C for 24 hours. The method used to determine water content was based on SNI 01-2891-1992, and antioxidant activity was determined using the UV. VIS spectrophotometry method. The data were analyzed according to descriptive analysis. The results indicated that the simplicia ginger and lemongrass powder in the oven drying method resulted in lower moisture content, higher antioxidant activity, stronger aroma quality, and lighter color compared to the conventional drying. The water content of ginger and lemongrass powder was 6.75% and 7.2% in oven drying, while the conventional methods were 7.25% and 10.15%, respectively. The antioxidant activity of ginger and lemongrass powder in oven drying was 65.12% and 51.63%, while the conventional methods were 62.41% and 50.05%, respectively. Based on this study, it can be concluded that the simplicia of ginger and lemongrass powder indicated the better characteristics and quality with the oven drying method at 50°C for 24 hours compared to the conventional method using open-air sun drying.